The Relationship Between Diet and Nutritional Status of Pregnant Women in the Third Trimester - Sinulingga, Yeni Friska; Sihaloho, Endang; Daulay, Evlindari Sentani; Ristiani; Nazara, Titin Sundari (Lembaga Teewan Journal Solutions, 2026)
The nutritional status of pregnant women is an important factor affecting maternal health and fetal growth. One factor that plays a role in determining nutritional status during pregnancy is diet. An unbalanced diet can increase the risk of nutritional disorders in pregnant women, especially in the third trimester when nutritional needs increase. This study aims to analyze the relationship between diet and the nutritional status of pregnant women in the third trimester. This study used an observational analytical design with a cross-sectional approach. The study was conducted at the Helen Tarigan Clinic in January 2026. The study sample consisted of 43 pregnant women in the third trimester selected using a total sampling technique. Dietary data were obtained through questionnaires, while nutritional status was assessed based on anthropometric measurements. Data were analyzed univariately and bivariately using the Chi-Square test with a significance level of 95%. Most respondents were aged 20–35 years (74.4%), had a high school education (46.5%), worked as housewives (60.5%), and were multigravida (58.1%). Pregnant women with good dietary habits were more likely to have good nutritional status (48.8%), while those with poor dietary habits were more likely to have poor nutritional status (25.6%). Chi-square test results showed a significant relationship between dietary habits and nutritional status of pregnant women in the third trimester (p=0.003). Dietary habits were significantly associated with nutritional status of pregnant women in the third trimester. Implementing a good dietary habit can help maintain optimal nutritional status during pregnancy.